Investigations on Performance of AI based System for Highways - et. al., Dr. Virendra Sangtani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this topic ,smart street lighting system supported the movement of any vichels Or Animals, Human using IR sensors is proceeds LED light (street light) control oà and on is about by the outputsupported the movement tracking using IR sensor. Street lights are the foremost requirement in day to daylifetime of transportation for safety purpose and avoiding accidents during night. Street lighting systems aregetting more complex with rapid climb of cities . to manage and maintain such complex street lighting systems,various street light control systems are developed. during this project, we are becoming to develop a project called Street Light Control using IR sensors ,in which the road lights are automatically turned ON or OFF supported the movement of the vehicles. The important considerations within the event of street light control systems are Automation, Powerconsumption and price Effective. However existing LED system is implementing to detect continuously but it'seconomically high and efficiency of the prevailing system is low. Therefor this project purpose to prevent thelosses of electricity and reduced the speed of accident , by Electively, Economically.